Furthering the discussion on the use of dynamical systems theory for investigating resilience in sport - Galli, N.; Pagano, K. (Sport, Exercise, and Performance Psychology, 2018)
In this commentary, we offer a critique of Hill, Den Hartigh, Meijer, De Jonge, and Van Yperen`s (2018) article, "Resilience in Sports From a Dynamical Perspective," in which they recommended the dynamical systems theory as a framework for the study of resilience in sport. Specifically, we rely on our research and practical experiences to call into question some of the author`s assertions. We suggest further clarification on what constitutes an interaction in the sport environment, more emphasis on precompetition athlete history in determining performance following failure, and further consideration of the role of athlete cognition. Recommendations for future research in sport resilience include examining the interactions in resilience through moderation-based statistical techniques and the potential for successive sport failures to promote personal growth. (PsycINFO Database Record (c) 2018 APA, all rights reserved)